A strategy for technology development for semi-arid sub-Saharan Africa - Sanders, J.H.; Shapiro, Barry I.; Ramaswamy, S. (1998)
This article proposes strategy for agricultural technology development for semi-arid West Africa. The strategy evaluation consists of two aspects: a) a review of the successes in the region; and b) analysis with mathematical programming of the potential impacts and constraints to various new technologies tested in the region. The technology development strategy indicates how further productivity gains can be made by responding to the two principal constraints of water availability and soil fertility. These constraints must be simultaneously resolved but the strategy needs to be adapted for different soil characteristics and economic environments. The major emphasis is on the importance of the rapid introduction of inorganic fertilizers combined with techniques to increase water availability; organic and inorganic fertilizers need to be considered complements in the semi-arid regions. Farmers are already introducing labour intensive variations of these techniques in the most degraded regions. The policy concern is to encourage government policy makers to put a high priority on fertilizer and increase the availability of inorganic fertilizer while research efforts continue to develop improved methods for complementary use of organic fertilizer.